Correlatos neurais do trauma infantil e comportamento suicida em adultos portadores de transtorno bipolar - Dante Galileu Guedes Duarte (2016)
BACKGROUND: Bipolar Disorder (BD) is a psychiatric disorder associated with high rates of suicide attempts (SA). The childhood-maltreatment (CM) is one of the main factors contributing to the onset and severity of suicidal behavior in patients with BD. Someneuroimaging studies have detected morphological changes in brain regions that make up the fronto-limbic network of adults with BD who suffered childhood-maltreatment and lifetime history of suicide attempt. However, the findings are heterogeneous and poorly replicable.OBJECTIVES: To evaluate gray matter volume (GMV) in regions of the the fronto-limbic network related to CM and SA in patients with BD. METHODS: We assessed 40 patients with BD type I and 20 healthy controls. The CM was assessed by childhood trauma questionnaire (CTQ) and suicide behaviour by Becks suicide scales. Voxel-basedmorphometry (VBM) was used for processing magnetic ressonance images. RESULTS: Bipolar patients showed an inverse correlation between total score of CTQ and trauma subtypes and GMV in the right dorsolateral prefrontal cortex and the right thalamus. The group of bipolar patients with SA history showed alteration of GMV in the right anteriorcingulate cortex, which was more pronounced in the high-lethality subgroup. Other findings of abnormalities in GMV were located in the orbitofrontal córtex and insula in high-lethal group. CONCLUSION: This study suggests that traumatic experiences in childhood and suicidal behavior are related to morphological abnormalities in neural networks that make up the fronto-limbic system in bipolar patients. The findings are crucial to the development of a science of preventative psychiatry and to the design of a neurobiological model.